2021
DOI: 10.1002/mp.14941
|View full text |Cite
|
Sign up to set email alerts
|

Physics‐based iterative reconstruction for dual‐source and flying focal spot computed tomography

Abstract: For single-source helical Computed Tomography (CT), both Filtered-Back Projection (FBP) and statistical iterative reconstruction have been investigated. However, for dual-source CT with flying focal spot (DS-FFS CT), a statistical iterative reconstruction that accurately models the scanner geometry and acquisition physics remains unknown to researchers. Therefore, our purpose is to present a novel physics-based iterative reconstruction method for DS-FFS CT and assess its image quality. Methods: Our algorithm u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…The reconstruction technology used in this experiment, iDose 4 , is an iterative reconstruction technology based on double space and multiple models introduced by Philips. It effectively removes noisy data, preserves the clarity of structural boundaries, reduces noise resulting from reduced radiation dose, improves image resolution, and maximally maintains image authenticity (34)(35)(36). Studies have shown that iDose 4 reconstruction technology ensures accurate diagnosis while significantly reducing radiation dose (18,37).…”
Section: Discussionmentioning
confidence: 99%
“…The reconstruction technology used in this experiment, iDose 4 , is an iterative reconstruction technology based on double space and multiple models introduced by Philips. It effectively removes noisy data, preserves the clarity of structural boundaries, reduces noise resulting from reduced radiation dose, improves image resolution, and maximally maintains image authenticity (34)(35)(36). Studies have shown that iDose 4 reconstruction technology ensures accurate diagnosis while significantly reducing radiation dose (18,37).…”
Section: Discussionmentioning
confidence: 99%
“…With this X source as a reference, subsequent interpolation, and reconstruction were then performed. e Z-axis interpolation algorithm of multisource variable-pitch spiral CT needed to take the more general Z-axis interpolation of cross-spiral, multilayer projection data into account when the pitch varied [17]. During interpolation, 2 projection rays located on both sides of Z and closest to Z R were sought among all projection rays parallel to ray (β, c).…”
Section: Msct Reconstruction Algorithmmentioning
confidence: 99%
“…For this reason, the circular-edge technique is becoming widespread as a methodology that can measure not only the performances peculiar to the system but also the properties of image quality in each task that depend on imaging conditions and processing algorithms. [ 18 19 20 ] This property is called as task-based rather than system specific.…”
Section: Introductionmentioning
confidence: 99%